A VASIVÍZ ZRt. gazdasági elemzése és a 2011. évi CCIX. víziközmű szolgáltatásról szóló törvény hatása - Berki Júlia (2016)
The topic of my thesis is the introduction and economic analysis of ‘VASIVÍZ’ Ltd. and the impact of the act of 2011 on water public utility service upon the company’s life. In the first part, I emphasized the activity of the company which deals with the most essential component of our life – water. It is a responsible task to exploit water from under the surface with high technology and transform it into drinking water and deliver to costumers. Besides this, with the help of EU tenders the company starts several pro-grammes to improve water quality, during which they change the old, outworn water-conduit. I also went into detail about how much the company cares about environmental protection. It is consciously and continually developing its environmental protecting activ-ity, which is being proved by the introduction of the “ISO” international standard and its continuous cooperation with environmental protection agencies. The main topic of my thesis is the economic analysis of the company and the im-pact of the act of 2011 on water public utility service upon the property- and financial situation of the company. The primal goal of the act is the protection of the property of water public utility, sustainable development and drinking water sources. Due to this, the property of water public utility got into the ownership of the competent local governments, which caused a waste of 7,8 billion HUF in 2013. One of the most determining conditions of the act is the dictation of the user quota which has to reach an amount of 150 thousand, otherwise the Hungarian Energy and Public Utility Regulatory Authority will deny the operating permit. Consequently, a lot of small waterworks joined the company, therefore the service territory was expanded by adding Celldömölk and its region, Sárvár and its region and Őrség to it. It was not easy to integrate these smaller waterworks, however, it was essential to gain the operating permit, so the company finally got it on November 7, 2013. The act fixes the principle of cross subsidization, according to which the service charge should be determined in a way that it provides coverage to the reasonable costs of the company and the input but does not cover any other type of costs. The new standard charge will be determined and approved by the parliament, which has caused severe data service responsibility in the company. Finally, I found it out that the companies of this branch have got into a tight corner and the transfer of property generated huge wastes in 2013. Furthermore, the unchanged charges, the utility cost reduction and further taxes set by the office caused great damage, however, each has to adjust to this centralized system, since there is no other way.